Changes in Semsc, Glucosinolates and Sulforaphane Levels, and in Proteome Profile in Broccoli (Brassica Oleracea Var. Italica) Fertilized with Sodium Selenate - Moenne-Munoz, A; Mahn-Osses, A; Barrientos-Carvacho, H; Barrientos-Carvacho, H (2013)
Sin Editorial Disponible